Control Environment and Operational Efficiency in SACCOs: a case study of Butuuro Peoples’ SACCO - Barigye, Benson; Ocan, Johnson; Akena Adyanga, Francis (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
The study assessed the influence of control environment on the operational efficiency in SACCOs using a case study of Butuuro SACCO. The primary data collected from members of the Board, Supervisory Committee, Elders (who served on the Board and retired) and staff of the SACCO was collected using self-administered questionnaires framed on the Likert scale of 1 to 5. The sample of 54 respondents was selected using Yamane formula. Individual respondents in the study were selected using simple random sampling techniques. The reliability of data was achieved using the Cronbach Alpha which was established at 0.851 for the control environment and 0.704 for operational efficiency. Collected data was analyzed using inferential statistics with the aid of Statistical Package for Social Scientists (SPSS) version 20. The results revealed a significant positive relationship between control environment and operational efficiency (r=0.472, P=0.000), control environment explains 22% (R2 =0.22) of variance in operational efficiency, the beta value for control environment from the regression model was 0.472 at p< 0.03. The study concludes that control environment has a significant positive association with operational efficiency. The study recommends a strong and effective environment for improving the operational efficiency of SACCOs.